Gambaran Rencana Pulang Warga Binaan pada Sebuah Lembaga Pemasyarakatan Perempuan di Indonesia: Studi Pendahuluan - Sayyidati Ummy Nurul Baity; Megah Andriany (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2019)
Introduction: As the development of the time, women committed criminal activities usually dominated by man. That crimes resulted negative stigma by society. So, it requires effective many discharge planning for female inmates to face the freedom. This study is useful for correctional nurses because of nurse basic role for provides female inmates discharge planning.Methods: The study about description female inmate’s discharge planning has already been studied in qualitative method, but it has not yet been studied in quantitative. The research purpose is to know the discharge planning of the return of the inmates in a female prison in Indonesia. This study was descriptive quantitative research method using with cross sectional approach. This research used questionnaire as the instrument. There were 25 samples that chosen by total sampling technique on a women’s prison in Indonesia. The analysis data using univariate analysis.Results: 92% of respondents would plan follow up skills from prisons, 68% of respondents would do legal plan, 100% of respondents would do the plan to maintain physical condition, 70.3% of respondents would do social interaction plan, 98% of respondents would do the mental spiritual plan, 65% of respondents would do the plan to meet the needs of residence and economy. Conclusion: There were various planning of female inmates before release from a prison. Correctional nurses are recommended to give more attention to the psychosocial problems of the women inmates and able to develop discharge planning program for the woman inmates by their freedom so that the inmates are ready to return to the society.